KLauS: a low power Silicon Photomultiplier charge readout ASIC in 0.18 UMC CMOS - Briggl, Konrad; Chen, Huangshan; Schimansky, David; Shen, Wei; Stankova, Vera; Schultz-Coulon, Hans-Christian (Journal of Instrumentation, 2016)
We present the development of a low power Silicon Photomultiplier charge readout ASIC for an imaging calorimeter at a future linear collider. The analog front-end is designed to achieve sufficient signal-to-noise ratio for single pixel signals using low gain SiPMs, while allowing charge measurements over the full dynamic range of the sensors. The front-end consists of an input stage, two charge measurement branches and a fast comparator. A SAR ADC with a resolution of 10 bit digitizes the pulse height information. An additional pipelined SAR stage allows to increase the quantization resolution to 12 bit for calibration measurements.
Gesehen am 19.05.2020